2013
DOI: 10.1128/aac.01578-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phenotypic Characterization of Hepatitis C Virus NS3 Protease Variants Observed in Clinical Studies of Telaprevir

Abstract: Telaprevir is a linear, peptidomimetic small molecule that inhibits hepatitis C virus (HCV) replication by specifically inhibiting the NS3·4A protease. In phase 3 clinical studies, telaprevir in combination with peginterferon and ribavirin (PR) significantly improved sustained virologic response (SVR) rates in genotype 1 chronic HCV-infected patients compared with PR alone. In patients who do not achieve SVR after treatment with telaprevir-based regimens, variants with mutations in the NS3·4A protease region h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
7
19
0
Order By: Relevance
“…Also, H77S.3 contains a reporter between p7 and NS2, both of which are important for viral assembly (12), and H77S.3 is not as well adapted to culture as the genotype 2a and 1a recombinants used in this study (20,23,71,72). Our study shows partial agreement with prior replicon studies, where A156T and A156V had a strong negative effect, while R155K, A156S, and T54A had either no effect or a moderate negative effect, on replication (34)(35)(36)(73)(74)(75)(76). Differences might be explained by the subgenomic nature of replicons and/or genotype/strain-specific differences.…”
Section: Discussionsupporting
confidence: 82%
“…Also, H77S.3 contains a reporter between p7 and NS2, both of which are important for viral assembly (12), and H77S.3 is not as well adapted to culture as the genotype 2a and 1a recombinants used in this study (20,23,71,72). Our study shows partial agreement with prior replicon studies, where A156T and A156V had a strong negative effect, while R155K, A156S, and T54A had either no effect or a moderate negative effect, on replication (34)(35)(36)(73)(74)(75)(76). Differences might be explained by the subgenomic nature of replicons and/or genotype/strain-specific differences.…”
Section: Discussionsupporting
confidence: 82%
“…NS5B variant R422K had replication capacities of 1% and 47% in genotype 1a and genotype 1b replicons, respectively. Similarly, the NS3 variant V36MϩR155K had a lower replication capacity in the genotype 1a replicon (20%) than that previously obtained in the genotype 1b replicon (42%) (33). Furthermore, the replication capacity of the NS3 V36A, A156T, and V36AϩR155K variants obtained in genotype 1b (6% to 20%) was lower than that previously determined in a different genotype 1b replicon (16% to 104%) (33).…”
Section: Susceptibility Of Vx-222-resistant Variants To Filibuvir Andmentioning
confidence: 45%
“…The replication capacity of variant replicons was determined as previously described (33). Briefly, replicon RNA was in vitro transcribed and transfected into Huh-7-ETcured cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in vitro measures of the telaprevir IC 50 and fitness for different variants observed by sequencing [18] suggested that there were five broad categories of resistance variants. These categories include: (I) low resistance, high fitness variants (e.g.…”
Section: Analysis Softwarementioning
confidence: 99%